The Factors Associated with the Placement of Neonatal ward at Prof. Dr. Margono Soekarjo Hospital - Fatma Qurrotunnada; Happy Dwi Aprilina (Proceedings Series on Health & Medical Sciences, 2022)
Background: Neonatal placement increases the need of perinatology room. The mortality rate of neonates in the perinatology room reached a progressive rate in Indonesia in 2021. Some severe conditions in neonates placed in the perinatology room included asphyxia, low birth weight, sepsis, and infection. The importance of segregating the neonatal ward in perinatology as a special treatment room for emergency conditions is to achieve optimal health and to reduce the mortality in neonates. Objective: The study aimed to determine the factors associated with the neonatal ward at Prof. Hospital Dr. Margono Soekarjo Purwokerto. Methode: This was an analytical observational study with a cross-sectional design. The study was carried out from March 24th-April 24th, 2022. The population in this study was 100 respondents. There were two groups of 50 respondents selected from the non-perinatology room and the perinatology room using a consecutive sampling technique. Result: The result showed that four significant factors were found that were associated with neonatal ward placement in perinatology based on the Bivariate analysis and Chi-Square test with 95% CI and a p-value of 0.05. They include birth weight (0.014), APGAR score (0.001), gestational period (0.003), and type of delivery (0.009). Then, the results of a multivariate analysis of the four factors indicated that the type of delivery was the most dominant (B=1.371). Conclusion: In this study, the variable of the type of delivery done by cesarean section was the most dominant factor in the placement of the neonatal ward in perinatology.